Commercial Agency Law. (2025)
Law no. 120/1982 dated 5/8/1982 – the law of organizing commercial agency and certain mediation activity operations – chapter 1: general provisions – chapter 2: obligations of commercial Agents, mediators and others – chapter 3: provisions related to contracts concluded by the government and the public sector – ministerial order no. 342/82 the executive regulation of law 120-82 promulgated law organizing commercial agency works and certain commercial intermediation